Undead Ed - Ghoulstone, Rotterly; Baines, Nigel (New York : Razorbill, 2012)
If dying on his thirteenth birthday was not bad enough, Ed Bagley becomes a putrid zombie pursued by his demonic, severed arm.
Hoping to reinvent himself as a more assertive individual when he is transformed into a zombie, thirteen-year-old Ed Bagley encounters challenges in the form of his own disembodied arm, a werewolf named Max, and a skeleton called Clive.
Keywords: Dead -- Fiction; Zombies -- Fiction; Supernatural -- Fiction; Horror stories; Dead -- Fiction; Zombies -- Fiction; Supernatural -- fiction; Humorous fiction; Humorous fiction; Horror fiction